Metaphor and Literalism in Buddhism - Hwang, Soonil (Routledge Critical Studies in Buddhism - Oxford Centre for Buddhist Studies, 2006)
Soonil Hwang studies the doctrinal development of nirvana in the Pali Nikaaya and subsequent tradition and compares it with the Chinese aagama and its traditional interpretation. He clarifies early doctrinal developments of Nirvana and traces the word and related terms back to their original metaphorical contexts, elucidating diverse interpretations and doctrinal and philosophical developments in the abhidharma exegeses and treatises of Southern and Northern Buddhist schools. The book finally examines which school, if any, kept the original meaning and reference of Nirvana.